Cytokines, growth mediators and physical activity in children during puberty (Medicine and Sport Science, 55, 2010)
Linear growth and sexual maturation are influenced by the actions of the endocrine system as well as by the nutritional status and level of physical activity of an individual. This publication focuses on the latest research regarding different physical growth and energy balance-related mediators in puberty. It summarizes the complex relationship between inflammatory mediators/cytokines, growth factors, body composition, physical fitness and physical activity of children and adolescents. Special emphasis in the book is placed on the role of various recently discovered inflammatory mediators/cytokines in the development of possible metabolic risk factors, in bone metabolism and other body composition parameters. Further, the book considers the adaptation to acute and chronic exercise in children during puberty and the development of possible menstrual irregularities. Health professionals, particularly pediatricians, exercise and sport scientists, coaches, researchers and students will find the book an excellent source of up-to-date information written by leading international experts in the field. (Autorreferat)